“El acta transaccional y su incidencia en la extinción de las obligaciones, en la notaría segunda del cantón Riobamba, en el año 2015.” - Vilema Adriano, Ligia Alexandra (2017)
In law and specifically in the Civil Code book IV, the obligations are determined in general and after having a thoroughly study we can clearly define that an obligation is a legal bond, in which a person is bound to another person to give, do or not doing something. The obligations that have been contracted by any title can be terminated in several ways but in particular we will focus our study on the transactional act; which is considered an instrument by which we can effectively terminate or prevent extrajudicial litigation that is more common in civil matters; because in criminal matters by its own nature is impossible to apply the transaction. Failure to comply with an obligation may initiate legal proceedings but we will determine that the law stipulates an effective way of culminating with this obligation that is the transaction. The transaction is a way to extinguish an obligation extrajudicially or to prevent a litigation, so it is considered an effective means to end a conflict provided the parties involved agree to agree above all, that agreement must not affect or harm any of the parties; but on the contrary, the parties finish with a satisfactory result. It is also important to mention that the transaction will only take effect in case the trial has not been judged; that is to say that the judgment has not had sentence at the moment of the transactional record celebration.